History of Fire Management in Medan during the Dutch Colonial Period - Suprayitno Suprayitno; Wara Sinuhaji; Deo Widika Alamsyah (Budapest International Research and Critics University, 2021)
Fire is a disaster that often occurs anywhere regardless of place and time, especially in areas with dense residential concentrations such as urban areas. Therefore, handling fire disasters is an important thing to be done properly so as not to cause casualties and minimize the damage that can result from the fire. Medan during the Dutch colonial period was a city with quite rapid growth in it, especially at the beginning of the 20th century. The increasing number of residents and buildings that stand in Medan is certainly a potential for situations that can cause a fire disaster at any time. Therefore, to be able to provide a sense of security to the residents of Medan from the threat of fire disasters, the Medan City government at that time formed a fire department in 1907 to be able to cope with any fire disasters that would occur in the middle of the city. The fire extinguishers in Medan during the Dutch colonial period certainly had their own challenges and methods based on the conditions and technology at that time in an effort to extinguish every fire that existed. This paper discusses how to handle fires carried out by the Medan City fire department during the colonial period. How to see their ways in anticipating fire disasters and see what resources they have in supporting their work to extinguish fires in the middle of Medan City at that time.